2018
DOI: 10.1007/s11356-018-2248-z
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized three-dimensional graphene sponges for highly efficient crude and diesel oil adsorption

Abstract: Modified Hummer's method has been used in this study to synthesize graphene oxide (GO) solution that was utilized for the fabrication of three-dimensional (3D) graphene sponges and their subsequent functionalization through a low-cost and facile vapor-based surface enhancement approach. The functionalized 3D-graphene sponge is an excellent absorbent, which can remove more than 3300 wt.% of crude oil (calculated with respect to the original sorbent mass). The functionalization of the obtained graphene sponges w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…General surveys related to 3D graphene‐based materials are less commonly found in recent literature. We can mention the works from Bagoole et al ., Gorgolis et al . and Yuan et al ., all published in 2017.…”
Section: Introductionmentioning
confidence: 99%
“…General surveys related to 3D graphene‐based materials are less commonly found in recent literature. We can mention the works from Bagoole et al ., Gorgolis et al . and Yuan et al ., all published in 2017.…”
Section: Introductionmentioning
confidence: 99%
“…In their first research paper that was published in 2007, the successful fabrication of a nanolubricant made of MWNTs and single-walled carbon nanotubes (SWNTs) was reported [20][21][22][23]. Moreover, the improvement in the thermal conductivity of the fabricated grease using CNTs was reported.…”
Section: Detailed Discussion About Grease Developmentmentioning
confidence: 99%
“…Furthermore, we believe that there is a need to develop a new procedure for CNT grease manufacturing as extensive experimental works have indicated that some grease needs only 1-2 wt% of the tube to form stable and homogeneous grease. The study of hydrogen bonding can be extended in the future to other nanomaterials with functional groups (such as OH, COOH, F, and NH), graphene, GO, and 3DrGO [23,35,36].…”
Section: Future Work and Commercial Applicationmentioning
confidence: 99%
“…Recently, there have been many reports showing the potential to prepare hydrophobic/oleophilic functional materials for oil–water separation 14 16 . For instance, Oscar et al 17 successfully fabricated the functionalized three-dimensional graphene sponges from graphene oxide solutions with different concentrations and trichloro(1H,1H,2H,2H-perfluorooctyl) silane. These advanced 3D graphene sponges showed excellent absorption efficiency of hexane solution.…”
Section: Introductionmentioning
confidence: 99%